Biosynthesis and characterization with antimicrobial activity of TiO2 nanoparticles using probiotic Bifidobacterium bifidum - Hkeem Ibrahem, Kawther; Ali, Fattma A.; Abdulla Sorchee, Sawsan M. (Cellular and Molecular Biology, 2020)
Bifidobacterium selectively colonizes the infants’ intestinal tract, and the relevant coliform bacteria in adults are particularly beneficial because of their enhanced capability to prevent pathogens of gastro intestine by direct antimicrobial action and relieve infection, which led to their intensification, the antibacterial activities of titanium nanoparticles producing by some bacteria, makes them attractive as a new agent against pathogenic bacteria. In our present study, we used a probiotic bacteria Bifidobacterium bifidum which was isolated from the commercial market capsule to produce TiO2 nanoparticles and study the biologically characterized nanoparticle using various techniques like Scanning Electron Microscopic (SEM), atomic force microscopy (AFM), and study its antimicrobial activity against a bacteria isolated from the stool of patients suffering from acute diarrhea. The results showed that the morphological characteristics of nanoparticles were found to have a spherical shape and mean size of 81 nm by AFM while scanning electron microscope viewed as an oval shape with anatase form synthesized by B. bifidum. TiO2-NP synthesized by B. bifidum had an inhibitory effect against P. aeruginosa, A. baumanii, K. pneumonia at a concentration 16 mg/ml and 32 mg/ml towards E. coli and S. typhi, the minimum inhibitory concentration (MIC) against pathogenic bacteria isolated from acute diarrhea included Pseudomonas aeruginosa, Acinetobacter baumanii, Klebsiella pneumonia, E.coli and salmonella typhi was utilized to determine the antibacterial impact of the synthesized TIO2 nanoparticles. Our biologically synthesized titanium nanoparticles were effective against all the tested pathogenic bacteria at various degrees and had a probable role in significantly greater antimicrobial efficacy against all isolates under study. This trial may have considerable significance for the prevention of antibiotic resistance associated diarrhea in hospitals.